1983
DOI: 10.1002/jcu.1870110204
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic mitral gradient without associated valvular stenosis: Usefulness of two‐dimensional echocardiography for a correct diagnosis

Abstract: A diastolic gradient across the mitral valve is generally indicative of mitral valve stenosis. In the present study, echocardiography was used to demonstrate two less common causes of left ventricular inflow obstruction: one patient had a fibromuscular membrane beneath the valve, the other a large vegetation attached to the posterior leaflet of the mitral valve. Echocardiography proved to be the optimal imaging technique in each case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…A milestone was reached in 1982 when Foale et al characterized an LAA aneurysm using transthoracic echocardiography (TTE) [13]; by 1983, German literature was reporting LAA aneurysm characterization using echocardiography and computed tomography [14]. Meanwhile, other European researchers were exploring the value of echocardiography and tomography in diagnosing endocavitary thrombi [15], establishing a foundation for axial imaging use in diagnosing, characterizing, and surgically planning for these patients [2]. Finally, in 1990, Frambach et al and Comess et al reported two cases diagnosed using TTE and transesophageal echocardiography (TEE), respectively [2,16].…”
Section: Discussionmentioning
confidence: 99%
“…A milestone was reached in 1982 when Foale et al characterized an LAA aneurysm using transthoracic echocardiography (TTE) [13]; by 1983, German literature was reporting LAA aneurysm characterization using echocardiography and computed tomography [14]. Meanwhile, other European researchers were exploring the value of echocardiography and tomography in diagnosing endocavitary thrombi [15], establishing a foundation for axial imaging use in diagnosing, characterizing, and surgically planning for these patients [2]. Finally, in 1990, Frambach et al and Comess et al reported two cases diagnosed using TTE and transesophageal echocardiography (TEE), respectively [2,16].…”
Section: Discussionmentioning
confidence: 99%